Tourism Marketing Communication as Institutional Practice: An Interpretive Study of Waduk Malahayu Promotion - Badriyah, Titin; Sumarlan, Iman (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2026)
This study examines how tourism marketing communication is practiced by a public tourism institution in promoting Waduk Malahayu. It adopts an interpretive qualitative approach using in-depth interviews, observations, and document analysis to analyze institutional communication practices. The analysis identifies a dominant orientation toward visibility, announcement, and institutional presence rather than toward sustained symbolic construction or relational engagement. Marketing communication activities are organized around episodic coordination, with events functioning as central moments of communication intensity and integration. Communication practices reflect a transmission-oriented conception in which integration occurs through temporal alignment rather than narrative coherence across channels and time. These practices are shaped by institutional logics associated with public-sector governance, including program-based planning and accountability demands. The study contributes to communication scholarship by conceptualizing tourism marketing communication as institutional communication and by demonstrating how integrated marketing communication is redefined through institutional enactment. The findings offer transferable conceptual insights for the study of public-sector communication and tourism promotion.